Portable Device for Monitoring the Respiratory Rate in Home Conditions - Arizmendi Flores, Sergio Alejandro; Contreras Fernandez Del Castillo, Carlos; Solana Carreón, Diego Santiago; Zenteno Barreiro, Sebastián; Brieva, Jorge; Ponce, Hiram; Moya-Albor, Ernesto (IEEE, 2023)
During the last decades, technological advances have escalated at astronomical levels. One of the fields where technology has proven to be the most beneficial is in medicine. The vital signs monitoring is one of the medical areas with greater advances. Despite this technological advance in monitoring vital signs, heart rate and oxygen saturation are the ones that continue to be most used in diagnosis to the detriment of respiratory rate (RR) in medical and non medical environments. In this work we propose a preliminary contact device easy to use in non medical environments for monitoring, measuring and recording the RR. We test our device in controlled conditions in five healthy subjects. Accuracy will be computed through comparison of a visible estimation of the RR and the acquired data. The obtained mean PE% is less than 6% in normal conditions of utilisation for the experiments. Overall, our device has proven a reliable tool for RR measurement in this preliminary version. © 2023 IEEE.
Keywords: Performance evaluation; Heart rate; Prototypes; Extraterrestrial measurements; Universal Serial Bus; Recording; Software reliability